Mexicans in California : Transformations and Challenges - Zavella, Patricia; Gutierrez, Ramón A., 1951- (Book collections on Project MUSE., 2009)
Numbering over a third of California's population and thirteen percent of the U.S. population, people of Mexican ancestry represent a hugely complex group with a long history in the country. Contributors explore a broad range of issues regarding California's ethnic Mexican population, including their concentration among the working poor and as day laborers; their participation in various sectors of the educational system; social problems such as domestic violence; their contributions to the arts, especially music; media stereotyping; and political alliances and alignments. Contributors are Brenda D. Arellano, Leo R. Chavez, Yvette G. Flores, Ramón A. Gutierrez, Aída Hurtado, Olga Nájera-Ramírez, Chon A. Noriega, Manuel Pastor Jr., Armida Ornelas, Russell W. Rumberger, Daniel G. Solórzano, Enriqueta Valdez Curiel, and Abel Valenzuela Jr.